A comparison on the factors that shape linguistic variation in chat room discourse of UiTM Sarawak students / Chan Ai Nyet and Linda Sim Yian Hua - Chan, Ai Nyet; Yian Hua, Linda Sim (Research Management Institute (RMI), 2012)
The rapid development in computer technology and the Internet has increased the popularity of Computer-mediated Communication (CMC) in chat rooms for interaction in all domains. The study on various types of CMC discourse is not new but the characteristics of and the variation within CMC are in flux. Many studies done on CMC have revealed contradictory findings. Besides, many researchers are unable to conclude that CMC should be labelled as speaking, writing, a combination of both, or neither. The need for research in this area, therefore, is ongoing. While the number of users of chat rooms is increasing, little is known about the reasons behind the wide variation in chat styles that chat users exhibit. This study aims to shed some light on the variations, first, the linguistic features and variation in chat room discourse of UiTM Sarawak students, and second to examine the contextual and individual factors influencing these linguistic features and variations found in the chat messages of the students. This study will analyse the chat room discourse of 22 UiTM Sarawak students. The data will be collected using three instruments - survey, online chat room, and interview. The survey will be used to gather background data on the participants. The transcripts of the chat room discussions will be analysed to find out what kind of linguistic styles and forms each individual uses in his or her discourse. T-Unit analysis and frequency analysis will be used to analyse all the participants' CMC transcripts. The face-to-face interview serves to garner information related to the individual and contextual factors affecting the language style and variation. The data gathered through the interviews will be analysed using the constant comparison method to identify the emerging contextual factors.